Study of the alternate bearing and some factors affecting it of local olive cultivar, Doaibli, in Tartous Governorate - Issa, ammar (Latakia University Journal -Biological Sciences Series, 2025)
The research was carried out in the 2022 and 2023 seasons in the village of Dahr Diba, in the Tartous Governorate in Syria, with the aim of studying the phenomenon of alternate bearing and the effect of some factors on the characteristics of flowering and fruiting of the local olive cultivar Doaibli. A factorial experiment was designed consisting of three factors: season (2022 and 2023), tree age (10 and 20 years), and harvest date (early and late). The results showed that Doaibli cultivar suffers from the phenomenon of alternate bearing, which causes large differences in productivity between seasons. It has been shown that the number of flowers per inflorescence is a cultivar dependent, and is not affected by the season, date of harvest, or the age of the trees. Also, alternate bearing affects the percentage of flowers with aborted ovaries, which increases with the increase in flowering load. It has been shown that the weight and size of the fruit increases in the year of lower fruiting compared to the year of heavy fruiting, and this applies to the weight of the kernel and pulp. The age of trees affects productivity and fruit weight. It also affects the percentage of flowers with aborted ovaries. It has also been shown that the date of harvest affects productivity. When fruits are harvested early, their productivity increases in the following year, and thus the severity of the alternate bearing decreases. We recommend harvesting the fruits of the Doaibali cultivar at the appropriate time, not delaying the harvest, and following various methods that limit the phenomenon of alternate bearing.